Forum Societatis revisited: commentary to the ECJ Judgment of 7 march 2018, c-560/16, e.On - Ballesteros Barros, Ángel María (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
ECJ Judgment of 7 March 2018, C-560/16, E.ON, clarify the scope of application of Article 22(2) of Council Regulation (EC) No 44/2001. The Court held that Article 22.2 must be interpreted as meaning that an action, such as that at issue in the main proceedings, for review of the reasonableness of the consideration that the principal shareholder of a company is required to pay to the minority shareholders of that company in the event of the compulsory transfer of their shares to that principal shareholder comes within the exclusive jurisdiction of the courts of the Member State in which that company is established. The author of this article disagrees with the reasoning used by the ECJ and proposes a different solution to the characterization of the action in the main proceedings.